Implementasi Pembelajaran Pendidikan Jasmani Olahraga Kesehatan Menggunakan Kurikulum Merdeka Di SMP Negeri Se-Kecamatan Bringin - Randy Chrisbinawan; Supriyono; Fery Darmanto; Ranu Baskora Aji Putra (Indonesian Journal for Physical Education and Sport, 2024)
The implementation of PJOK learning in public junior high schools in Bringin District is only one school that has entered an independent school, the other two schools are still ordinary schools and the implementation stages of each school in public junior high schools in Bringin District are unknown. The purpose of this study is to analyse how the implementation of PJOK learning using the independent curriculum in public junior high schools in Bringin sub-district. This research is a survey-based qualitative. The method used is qualitative research method. Data collection techniques are interviews, questionnaires, and documentation. The research instruments were interviews from teachers and questionnaires from students. Data validity technique is using triangulation table. The results of this study are that all public junior high schools in Bringin Sub-district have implemented an independent curriculum with the stages of implementation, namely SMPN 1 Bringin in the ready stage, SMPN 2 Bringin in the developing stage, and SMPN 3 Bringin in the developing stage. The conclusion of this study is that all public junior high schools in Bringin District have implemented an independent curriculum in PJOK learning and the stages of PJOK learning implementation using an independent curriculum, namely SMPN 1 Bringin at the ready stage, SMPN 2 Bringin at the developing stage, and SMPN 3 Bringin at the Developing phase